Dietary Fiber as a Counterbalance to Age-Related Microglial Cell Dysfunction - Vailati-Riboni, Mario; Rund, Laurie; Caetano-Silva, Maria Elisa; Hutchinson, Noah T.; Wang, Selena S.; Soto-Díaz, Katiria; Woods, Jeffrey A.; Steelman, Andrew J.; Johnson, Rodney W. (Frontiers in Nutrition, 2022)
With increasing age, microglia shift toward a pro-inflammatory phenotype that may predispose individuals to neurodegenerative disease. Because fiber fermentation in the colon produces bioactive short chain fatty acids (SCFAs; e.g., acetate, butyrate, propionate) that signal through the gut-brain axis, increasing dietary fiber may prevent or reverse age-related dysregulation of microglia. Adult (3-4 month old) and aged (23-24 month old) male and female mice were given ad libitum access to a modified AIN-93M diet with 1% cellulose or the same diet with 2.5% or 5.0% inulin for eight weeks. Several adult and aged male mice fed 0 or 5% inulin were randomly selected for whole brain single cell RNA sequencing (scRNA-seq) and differential gene expression analysis to classify brain microglia according to gene expression profile; and identify additional genetic markers of aging as possible targets for dietary interventions. Microglia were isolated from remaining mice and expression of selected aging-, inflammatory-, and sensome-related genes was assessed by Fluidigm as was the ex vivo secretion of tumor necrosis factor-alpha (TNF-α). SCFAs were measured in samples collected from the cecum. Microglia from adult and aged mice segregated into distinct phenotypes according to their gene expression profile. In aged mice, a considerably greater proportion of the population of microglia was identified being “activated” and a considerably smaller proportion was identified being “quiescent”. These findings using whole brain scRNA-seq were largely corroborated using highly purified microglia and Fluidigm analysis to assess a selected panel of genes. Aged mice compared to adults had lower levels of SCFA’s in cecum. Dietary inulin increased SCFAs in cecum and mostly restored microglial cell gene expression and TNF-α secretion to that seen in adults. Sex differences were observed with females having lower levels of SCFAs in cecum and increased neuroinflammation. Overall, these data support the use of fiber supplementation as a strategy to counterbalance the age-related microglial dysregulation.